Cross-Sectional Evidence of a Signaling Pathway from Bone Homeostasis to Glucose Metabolism - Gravenstein, Kristofer S. (Endocrine Society, 2011)
CONTEXT: Preclinical studies suggested the existence of a signaling pathway connecting bone and glucose metabolisms. Supposedly leptin modulates osteocalcin bioactivity, which in turn stimulates insulin and adiponectin secretion, and β-cell proliferation. OBJECTIVE: The objective of the investigation was to study the reciprocal relationships of adiponectin, leptin, osteocalcin, insulin resistance, and insulin secretion to verify whether such relationships are consistent with a signaling pathway connecting bone homeostasis and glucose metabolism. DESIGN: This was a cross-sectional analysis. SETTING: The study was conducted with community-dwelling volunteers participating in the Baltimore Longitudinal Study of Aging. PARTICIPANTS: Two hundred eighty women and 300 men with complete data on fasting plasma adiponectin, leptin, and osteocalcin, oral glucose tolerance test (plasma glucose and insulin values available at t = 0, 20, and 120 min), and anthropometric measures participated in the study. MAIN OUTCOME MEASURES: Linear regression models were used to test independent associations of adiponectin, osteocalcin, and leptin with the indices of insulin resistance and secretion. The expected reciprocal relationship between different biomarkers was verified by structural equation modeling. RESULTS: In linear regression models, leptin was strongly associated with indices of both insulin resistance and secretion. Both adiponectin and osteocalcin were negatively associated with insulin resistance. Structural equation modeling revealed a direct inverse association of leptin with osteocalcin; a direct positive association of osteocalcin with adiponectin; and an inverse relationship of osteocalcin with insulin resistance and adiponectin with insulin resistance and secretion, which is cumulatively consistent with the hypothesized model. CONCLUSIONS: Bone and glucose metabolisms are probably connected through a complex pathway that involves leptin, osteocalcin, and adiponectin. The clinical relevance of such a pathway for bone pathology in diabetes should be further investigated.